Development of an Optimization Scheme for A Fixed-Wing UAV Long Endurance with PEMFC and Battery - Al Rayes, Zaid (2018)
A Master of Science thesis in Mechanical Engineering by Zaid Al Rayes entitled, “Development of an Optimization Scheme for A Fixed-Wing UAV Long Endurance with PEMFC and Battery”, submitted in May 2018. Thesis advisor is Dr. Mohamed Gadalla. Soft and hard copy available.